The challenges of human resources for information communication technologies (ICTs) in Nigerian universities libraries (2003)
The paper examines the scenario and challenges associated with Information Communication Technologies (ICTs) with particular focus on human resources (HRs) well-equiped with know- how and skills for innovative adaptations of ICT utilisationk in Nigerian universities libraries. It identifies and discusses the need for availability of "Appropriate Human Resources" i.e. a calibre of ICThumanresources well-equipped with know-how and skills for innovative adaptations of ICT utilisation in Nigeiran Universities Libraries(NULs). The paper also stresses that the technological salvation of Nigerian Universities libraries (NULs). The paper also stresses that the technological salvation of Nigerian Universities libraries lies not in their perpetual dependence on technologically equipped expatriates and thier agencies, rather it lies in thier ability to evovle internally generated programmes for appropriate human resources development aimed at providing indigenous ICT capacity for adaptive and innovative ICT utilization within their specific local environments. It also emphasises that this is a way for Nigerian Universities Libraries to move from being just ICT consumers to being ICT producers for the benefits of thier patrons.